Operational Crisis Management Techniques in The Catering Industry in Times of Recession: The Case Of the Municipality of Piran - Kukanja, Marko; Planinc , Tanja (Naše gospodarstvo/Our economy, 2013)
This study examines crisis management techniques in the catering industry. The sur- vey was conducted in the municipality of Piran, the most developed Slovenian municipality in terms of tourism and an important tourist center in the northern Mediterranean. This paper investigates the response of the catering industry to the economic crisis by analyzing the use of different micro-level crisis practices in the catering industry. The study uses a questionnaire to evaluate the importance and usage of different crisis management techniques in the catering industry. The findings indicate a high level of inconsistency between the importance and usage of crisis management techniques. Government assistance is by far the most important and most used technique in times of crisis. Suggestions for future research and useful information for managers of catering facilities are provided.